2020
DOI: 10.1371/journal.pone.0238534
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling socioeconomic inequalities of type 2 diabetes mellitus in Chile: A population-based analysis

Abstract: Introduction Chile experiences a growing prevalence of DM2 in its adult population over time. The country has prioritised the diagnosis and treatment of DM2 through a universal health care package, largely focused on the clinical dimensions of the disease. We analysed the significance of socioeconomic variables in the prevalence of DM2, as well as its related dimensions of presence of complications (diabetic foot and ophthalmologic complications), attendance to health checks and acquisition of recommended life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
1
4
0
1
Order By: Relevance
“…In terms of socioeconomic inequality, our study indicated that diabetes and prediabetes are more prevalent among less educated people and among people with lower wealth scores. These findings are consistence with the studies conducted in other countries 11,63 . A study conducted by Al-Hanawi et al in Saudi Arabia indicated that diabetes prevalence was concentrated among the poor and among people with less education.…”
Section: Prediabetessupporting
confidence: 91%
“…In terms of socioeconomic inequality, our study indicated that diabetes and prediabetes are more prevalent among less educated people and among people with lower wealth scores. These findings are consistence with the studies conducted in other countries 11,63 . A study conducted by Al-Hanawi et al in Saudi Arabia indicated that diabetes prevalence was concentrated among the poor and among people with less education.…”
Section: Prediabetessupporting
confidence: 91%
“…The same occurs when analyzing other outcomes such as life expectancy or disability-free life expectancy, where it has been documented that people with a better socioeconomic position live longer and healthier lives compared to the more vulnerable population [ 16 ]. Even diseases as prevalent as Diabetes Mellitus II also follow a marked socioeconomic gradient when analyzed by quintiles of household income and educational level, where they also remain significantly associated with the presence of complications and attendance at health check-ups [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…These include factors driving not only incidence and increased exposure to the virus, 3 such as more precarious employment conditions, loss of income and the need to work outside the home, but also an increased prevalence of conditions that aggravate the consequences of the disease, which show a strong social patterning in Chile. 8 Mitigating health inequities was an explicit objective of the Chilean National Health Strategy 9 and the aggravation of these inequities amidst the COVID-19 pandemic represents a step in the wrong direction. Our analysis is limited by the lack of individual-level mortality data and a validated SES index.…”
mentioning
confidence: 99%